An in vitro bone-to-bone adhesion test method using the compression shear test. (December 2021) - Lührs, Vanessa; Stößlein, Sebastian; Thiel, Karsten; Grunwald, Ingo; Hartwig, Andreas
Abstract: The development of new bone adhesives is severely restricted due to the lack of a standard test method to examine their bond strength. Therefore, this study presents an in vitro bone-to-bone adhesion test method based on a compression shear test using cortical bone specimens (35 × 15 × 3 mm). The zero-gap lap joint test configuration was used to measure the bonding strengths of two soft tissue adhesives (Histoacryl® and BSA-Glue) and a bone cement (Palacos® LV). For reproducible bonding results, it is crucial to work with specimen having reproducible surface, dimensions and where and how they were taken from a bone. Therefore, this is a focus of the work. The adhesive strengths were determined under dry and physiological conditions to evaluate the reliability of the test procedure. Furthermore, the influence of previous acid etching of the bone surface was also investigated. The adhesives achieved bond strengths of 5.5 MPa (Histoacryl®), 3.2 MPa (BSA-Glue) and 2.8 MPa (Palacos® LV) under dry conditions. Under physiological conditions, the measured adhesive strengths of all three bonding materials decreased by around 90%. The acid etching led to a higher presence of reactive amino groups on the bone surface and improved the adhesion of Histoacryl® and BSA-Glue. The Palacos® LV bone cement suffered a reduction in adhesion as the acid smoothened the bone surface, resulting in less mechanical interlocking. The proposed test method is based on known standards and enables the usability of medical adhesives as a bone adhesive to be evaluated in a reproducible manner.